2011
DOI: 10.1186/1478-7547-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of continuous glucose monitoring and intensive insulin therapy for type 1 diabetes

Abstract: BackgroundOur objective was to determine the cost-effectiveness of Continuous Glucose Monitoring (CGM) technology with intensive insulin therapy compared to self-monitoring of blood glucose (SMBG) in adults with type 1 diabetes in the United States.MethodsA Markov cohort analysis was used to model the long-term disease progression of 12 different diabetes disease states, using a cycle length of 1 year with a 33-year time horizon. The analysis uses a societal perspective to model a population with a 20-year his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 20 publications
3
68
1
3
Order By: Relevance
“…McQueen and colleagues found a somewhat lower ICER of $45 033/QALY but this also did not include cost-reduction from severe hypoglycemia avoidance. 68 Ly and colleagues estimated the incremental cost of RT-CGM as part of a LGTS system and did include the costs associated with severe hypoglycemic events such as hospital admission, accidents, emergency visits, and ambulance calls. They found that the cost per QALY was AUS$40 803 in patients ≥12 years.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…McQueen and colleagues found a somewhat lower ICER of $45 033/QALY but this also did not include cost-reduction from severe hypoglycemia avoidance. 68 Ly and colleagues estimated the incremental cost of RT-CGM as part of a LGTS system and did include the costs associated with severe hypoglycemic events such as hospital admission, accidents, emergency visits, and ambulance calls. They found that the cost per QALY was AUS$40 803 in patients ≥12 years.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…1,2 In these analyses, the authors use health economic models and assumptions to investigate whether the use of CGM systems optimizes glycemic control to such an extent that the reduction in the cost of treating diabetes-related complications outweighs the cost of using the CGM systems or even makes their use cost saving. Usually, quality-adjusted life years gained and the corresponding incremental cost-effectiveness ratio are calculated to provide evidence for cost-effectiveness.…”
Section: Cost-benefit Analysis Of Continuous Glucose Monitoring Systemsmentioning
confidence: 99%
“…A good cost-utility ratio for CGM is particularly important where reimbursement is to be obtained for the device. Two studies have evaluated this ratio [53,54].…”
Section: Cost-utility Analysis Of Cgmmentioning
confidence: 99%